School for what? Reflections about the functions of public schools in the State of São Paulo - Raab, Yeda Strada (2019)
Although some research approaches the function of the school, this has been a subject almost always treated secondary in these researches. In this sense, it is relevant to approach this theme, considering that the phenomena studied in the school everyday are crossed by intentionalities that imply in this social function, which, inevitably, interferes in the other phenomena that characterize the school day to day. Thus, with the intention of thinking about the role of the State School of São Paulo in Basic Education, believing that the school does not explain itself, but through the relationship established with society, this text presents research results that sought to identify and analyze the function attributed to the São Paulo state public school expressed in official documents, as well as the one elaborated by teachers and students. In order to do so, we used the analysis of official documents that guide the operation of the public school in São Paulo, as well as collective semi-structured interviews with a group of students and a group of teachers from a school in that network. From the articulation of the participants' views with the theoretical reference and the analysis of the official documents, it is possible to consider that this school, which serves the working class, has based its function on a proposal of limited education, disseminating basic knowledge for work, distancing itself too much from the socialization of knowledge and the production of this knowledge.